As teorias da comunicação aplicadas à narrativa transmídia - Miranda, Gabriela Dischinger (2017)
From a brief overview of the main communication theories we can see that many that are still used today were thought between the decades of 1930 and 29160, based on mass communication; media that assumes asymmetric communication and one to many. Communication on digital media, on the other hand, is two way, in which the individual not only has the possibility to send their own messages, bus also respond to those they receive. Therefore, new digital media changed radically the communication environment, making it important to review the main communication theories seeking to identify those that can still explain multimedia and transmedia communication. In this dissertation, we mapped these main communication theories and detailed how digital and transmedia communication works. With four case studies we illustrated how communication happens today and looked for those communications theories that still fits in this scenario